The Role-Playing Type of Cooperative Learning Model Assisted by Digital Comic Media on the Social Attitudes of Grade IV Elementary School Students - I Gede Bagus Markandeya; I Gusti Agung Ayu Wulandari; Ni Luh Putu Agetania (Universitas Pendidikan Ganesha, 2025)
Low social attitudes among students in learning activities pose a significant issue, as it affects their ability to interact, collaborate, and empathize within the school environment. One contributing factor is the lack of innovative learning models that can optimally foster students' social attitudes. This study aims to examine the effect of the cooperative learning model of the role playing type assisted by digital comic media on students' social attitudes. This research employed a quasi-experimental design with a non-equivalent post-test only control group design. The study involved 56 fourth-grade elementary school students selected through cluster random sampling and divided into an experimental group and a control group. Data were collected using a non-test method in the form of social attitude observation sheets and analyzed using an independent sample t-test. The results showed that the tvalue = 4.276 > ttable = 1.670 at a 5% significance level, indicating a significant effect of the cooperative role playing model assisted by digital comics on students' social attitudes. It can be concluded that this learning model effectively improves students' social attitudes. The findings imply that the cooperative role playing model with digital comic media is a feasible and effective alternative strategy for developing students’ social attitudes in elementary education.